Intervention in coronary bifurcation lesions: Staying on top of the proximal optimization technique (POT). Issue 1 (11th July 2020) - Seth, Ashok; Singh, Vivudh Pratap
Key Points: Proximal optimization technique (POT) restores the stent to the fractal geometry of coronary bifurcations and is the final step when using two‐stent strategy. Optimal positioning of balloon during final POT is vital to achieve best results without side branch compromise. In vitro studies provide valuable insights to define procedural strategies and help achieve best outcomes for coronary bifurcation lesions.